Developing Conceptual Business Model for IOT Based Smart Energy Consumption - Asfoura, Evan; Kassem, Gamal (International Journal of Energy Economics and Policy, 2025)
This paper aim to develop a generic business model that is based on the literature review and can be applied in any country. This business model will rely on the Internet of things technologies of smart cities to provide energy consumers with information about their total and appliance energy consumption. When consumers reach a certain limit that they set for energy consumption, they can utilize renewable energy sources and users can choose the energy provider company that best suits their needs and preferences and dynamically switch between them to get the best price schemas. As well as this paper is to analyze the Egyptian market from an expert’s point of view and obtain insights from a user’s point of view. Lastly, this paper is to build a basic prototype to demonstrate how the energy management solution can work and how the user can be notified when his total energy consumption has exceeded a certain limit. The results will be quantitatively and qualitatively evaluated through distributing survey and conducting interviews in the Egyptian market.